Implementasi Model Pembelajaran Bermain Peran (Role Playing) Dalam Upaya Meningkatkan Pemahaman Siswa Terhadap Konsep Perbandingan Senilai Dan Berbalik Nilai (Ptk Siswa Kelas Vii Semester Gasal Smp Kasatriyan 1 Surakarta Tahun 2016/2017) - Ariyani, Putri Tika; Dra. Sri Sutarni,, M.Pd (2017)
ABSTRACT The background of this study is the lack of students' understanding of the concept of worth and turned comparison value of class VII A in junior High School Kasatriyan 1 Surakarta. The purpose of this study to find out the enhancement on students' understanding of the concept of worth and turned comparison value by applying the implementation of learning models named play a role (role playing) with the subject of class VII A junior Kasatriyan 1 Surakarta academic year 2016/2017. The kind of this research is classroom action research. The technique of collecting data through observation, testing, field notes, and documentation. The results showed an enhancement on students' understanding of the concept of views: 1. Declare the concept before applying the treatment about 6 students (28.6%) after treatment, it is increased to 17 students (80.95%). 2. Classify the objects based on the specific characters before applying the treatment about 4 students (19.05%) after the treatment applied, it is increased to 15 students (71.43%). 3. Give the examples and non-examples of the concept before applying the treatment about 4 students (19.05%) after applying the treatment, it is increased to 17 students (80.95%). 4. Apply the concepts or algorithms in solving the problems before applying the treatment about 2 students (9.52%) after applying the treatment, it is increased to 13 students (61.9%). Based on the research result, it can be concluded that the implementation of learning model named play a role (role playing) can enchance students' understanding of the concept of worth and turned comparison value.